EFFECTIVENESS OF THE PROGRAM OF EMPOWERMENT OF THE WOMEN RESIDING AT THE COASTAL AREA OF AMPENAN DISTRICT, MATARAM CITY, LOMBOK IMPLEMENTED IN THE FORM OF LIFE SKILLS - Listiawati, Ni Putu; Mariyah, Emiliana; Kutha Ratna, I Nyoman; Semadi Astra, I Gde (E-Journal of Cultural Studies, 2012)
The program of the empowerment of the women living in Mataram City implemented inthe form of life skills including vocational skill, social skill, and personal skill has been carriedout since 2001. In reality, the attempts already made could not improve the well-being of thewomen in Mataram City in general and the women living along the coastal area of Ampenan,South Ampenan District and Banjar District in particular. Based on the background mentionedabove, the researcher was interested in exploring the effectiveness of the program of theempowerment provided in the form life skills. Three problems are formulated in this research.They are (1) how effective the implementation of the empowerment program of the womenresiding at the coastal area of Ampenan District was?; (2) what factors contributed to theeffectiveness of the empowerment program of the women residing at the coastal area?; (3) whatwere the effects and meanings of the effectiveness of the empowerment program of the womenresiding at the coastal area? The theories employed to answer the problems formulated above arethe theory of post feminism by Ann Brooks, the theory of social practice by Bourdieu and thetheory of power/knowledge by Foucault. The theories were eclectically applied. The qualitativemethod was employed in this study and the data needed were collected by the techniques ofobservation, in-depth interview, Focus Group Discussion (hereon abbreviated to FGD),documentation and library research.The results of the study show that (1) the program of the empowerment of the womenliving in the coastal area was ineffective; (2) the factors which contributed to the effectivenessof the empowerment of the women living along the coastal area are economic capital, culturalcapital, socio culture and symbolic culture; (3) the effects of the effectiveness of theempowerment program were on the skills acquired, the income earned, the independenceacquired, the environment where they live and their pattern of consumerism. The meanings feltby one third of the women empowered were the meaning of awareness, the meaning ofsolidarity, and the meaning of being independent.In relation to this research, several things are suggested; (1) it is necessary to continue theempowerment program for the women living at the coastal area with the development ofpersonal and social skills as the priority; (2) it is necessary for the government to build a qualitytechnological, informational and communicative network in the form of educative informationalcenters at the coastal area; (4) it is time to establish vocational schools, which are accessible tothe local people, starting from the basic level to middle level in which skills how to managecoastal areas and sea would be provided. If it is possible, such schools should be free of charge;(5) further research needs to be conducted to understand the characteristics of the women livingalong the coastal area of Ampenan.
Keywords: empowerment, women residing at coastal area, life skills, effectiveness